Flow as a Metaphor for Changing Composition Practices. Issue 2 (3rd April 2017) - Green, David
Abstract: Given that research in language and literacy studies proffers multilingual and translingual literacy studies as central to contemporary English studies, English studies can benefit from increased attention to hip-hop language practices. While some linguists have argued for closer analysis of hip-hop nation language (HHNL) because of its relevance to youth identities and promise for critical language pedagogies, I argue that the concept of flow within HHNL studies has been largely overlooked for its value to the rhetorical development of students in English studies. While some linguists have employed the concept of flow to discuss the global movement of Black English across the globe and its implications for English as a lingua franca, flow also highlights the manner and means that artists use to move between ideas, concepts and dispositions in their compositions and therefore becomes valuable to the way English teachers may teach, study and discuss with students the possibilities of language. Because, surprisingly, academic writing is still too often viewed as a unified discourse that privileges edited American English above rhetorical fluency, flow provides an interesting way of repositioning writing and linguistic pluralism for students by focusing discussions of language and composing on features such as rhythm, vernacular eloquence, and layering and rupture in ways that press for newer considerations of language and literature within English studies.